Evolution of inguinal hernia surgical treatment - Belay, A. I.; Klimenko, A. V.; Rusanov, I. V. (Zaporozhye Medical Journal, 2013)
The article shows the data of modern specialized literature concerning the treatment of inguinal hernia. It presents the modern methods of laparoscopic hernioplasty as well as their advantages and disadvantages.